Zoonotic Transmission and Infection from Bovine Feces in Selected Ricefields of Lake Mainit, Philippines - Jumawan, Joycelyn C.; Balamad, Maria Karla M.; Estaño, Leonardo A. (Asian Journal of Biological and Life Sciences, 2020)
Ricefields are suitable nidus of active parasite transmission via bovines due to often unprotected exposure by humans and livestock that utilize the habitat for farming and foraging. This study was conducted to assess infection of protozoans, trematodes and nematodes from bovine feces from ricefields of Brgy Magpayang, San Isidro and Matin-ao surrounding Lake Mainit, Philippines. Bovine fecal samples collected from these ricefields were processed using the Formalin Ethyl Acetate Sedimentation (FEA-SD) technique. A total of five species from three major parasite groups (protozoans, trematodes and nematodes) were observed. Bovines from ricefields of Brgy San Isidro harbored the highest number of fecal parasites. The liver flukeFasciolasp. was the most predominant species observed with the highest prevalence (69%) across study areas. In contrast, multiple parasite burden ofFasciolasp., hookworms, coccidian oocysts andAscarissp. eggs were observed from bovines from Brgy San Isidro and Matin-ao. This study is the first report of parasites from bovine feces in selected ricefields of Lake Mainit. The high prevalence of Fasciola eggs in bovines calls for an extensive assessment of possible widespread bovine fascioliasis in the area.
Keywords: Bovines; Lake Mainit; Parasites; Zoonosis Fascioliasis